ANALISIS KELAYAKAN PENGEMBANGAN BISNIS PENGGEMUKAN SAPI STUDI PADA PETERNAKAN SAPI DI LAMPUNG TIMUR - Inka Riyani (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2020)
Need for beef continues to increase so that it requires an increase in local beef production to meet these needs. The purpose of this study was to determine the feasibility of developing a beef cattle business from financial and non-financial aspects. The research method used is qualitative research. The data obtained from the results of the research were then analyzed using descriptive quantitative data analysis using the formula NPV, Net B / C, IRR, Payback Period, and BEP. Based on the research results, it shows that Mr. Romi's beef cattle fattening is carried out by looking at the large opportunity in the market aspect. In the technical aspect of Mr Romi's beef cattle business, he has also been doing well, Mr Romi has chosen a feeder of superior quality. The fattening business has also been used. Fattening that was established by Mr. Romi has been made with due regard to environmental aspects by staying away from residents' houses so as not to be exposed to pollution from cow dung. The results of the risk analysis show that the handling of risks to Mr Romi's beef cattle fattening is carried out properly, namely by treating the sick cows appropriately so that the cows recover quickly and are healthy as before, the risk of death can be avoided by immediately treating the sick cows or selling them immediately to buyers. before dying. The risk of falling market prices due to beef imports can be faced by following market prices. Meanwhile, the risk of feeder cattle failing to grow in Mr Romi's cattle fattening is faced by buying feeders from high quality and fast breeders. The results of the business feasibility analysis through the Payback Period analysis, NPV, IRR, Net B / C and BEP are stated to be profitable for entrepreneurs from a financial aspect so that it can be said that Mr Romi's beef cattle business is feasible to be developed.